Breast fine-needle aspiration cytology in the era of core-needle biopsy: what is its role? - Ahrong Kim; Hyun Jung Lee; Jee Yeon Kim (Journal of Pathology and Translational Medicine)
Fine-needle aspiration cytology (FNAC) has long been recognized as a minimally invasive, cost-effective, and reliable diagnostic tool for breast lesions. However, with the advent of core-needle biopsy (CNB), the role of FNAC has diminished in some clinical settings. This review aims to re-evaluate the diagnostic value of FNAC in the current era, focusing on its complementary use alongside CNB, the adoption of new approaches such as the International Academy of Cytology Yokohama System, and the implementation of rapid on-site evaluation to reduce inadequate sample rates. Advances in liquid-based cytology, receptor expression testing, molecular diagnostics, and artificial intelligence are discussed, highlighting their potential to enhance the diagnostic accuracy of FNAC. Despite challenges, FNAC remains a valuable diagnostic method, particularly in low-resource settings and specific clinical scenarios, and its role continues to evolve with technology.